A novel s-box generation method based on metastable inducing over FPGA for block ciphers - Garipcan, Ali Murat; Aydin, Yilmaz; Ozkaynak, Fatih (Elsevier, 2025)
Substitution boxes (s-boxes) providing the nonlinearity property are fundamental components of modern encryption systems. The security of these systems directly depends on the quality of the s-boxes ensuring a high level of resistance to advanced attacks. Although there is no perfect method in the literature, improving the cryptographic properties of s-boxes, such as nonlinearity and differential independence remains an important area of interest for many researchers. In this paper, we propose a new s-box generation method based on the reinforcement of the randomness obtained from the metastable states of the R-S latch. In the proposed method, a Field Programmable Gate Array (FPGA) chip is used to obtain design inputs based on physical reality obtained from the hardware level. Design inputs with poor statistical adequacy are transformed into s-boxes by passing them through four different hash functions (Blake2b, Blake2 s, SHA3 and Shake). A total of 333,328 s-boxes are generated with the proposed method for four different scenarios and widely used evaluation metrics such as bijectivity, nonlinearity (NL), strict avalanche criteria (SAC), bit independence criteria (BIC), differential probability (DP) and linear probability (LP) are considered for the analysis. Taking into account these metric values, the study also presents a detailed performance comparison of the proposed s-boxes with recent studies from the last 5 years in the literature. The fact that the nonlinearity degree of 75 % of the produced s-boxes is higher than 103, which is the average limit value in the literature, also confirms the method's efficiency, proven reliable by the analysis results. When all these results are evaluated together, they confirm that the proposed method is highly effective in generating robust s-boxes and that these s-boxes can be reliably used in modern cryptographic systems.
Keywords: Substitution box; Block ciphers; Cryptography; Hash functions; Field programmable gate array